The Reluctant Participant - Bilodeau, Annik (Imagining SoTL, 2025)
This piece is a creative reflection on my experience with Pop-Up Poetry at the 2024 SoTL Symposium in Banff, in which I consider the intersection of identity, academia, care, and community.